Additive manufacturing of a bridge in situ. Issue 2 (22nd April 2022) - Feucht, Thilo; Waldschmitt, Benedikt; Lange, Jörg; Erven, Maren
Abstract: Nominated for Eurosteel 2021 Best Paper Award Additive manufacturing (AM) is playing an increasing role in the production of complex steel structures. Robot‐ or machine‐guided gas‐shielded metal arc welding (GMAW), known as wire and arc additive manufacturing (WAAM), is suitable for this purpose. A small footbridge was designed in shell form at TU Darmstadt. It was completely additively manufactured over a stream on site using a welding robot. The work called for cantilevered manufacturing without support structures, which poses special challenges in manufacturing. This paper describes selected aspects of this project: the preliminary strength studies, the manufacturing strategy to ensure homogeneous manufacturing and the findings from on‐site manufacturing. In addition, investigations were carried out which led to a notable increase in the deposition rate with the right choice of gas and wire.